PELATIHAN JUALAN ONLINE UNTUK UMKM PEMULA DI ERA DIGITAL - arumsari, kusuma; Nurhayati; Fardhoni; Lisa Astria Milasari (Forum Komunikasi Dosen, 2025)
In today's digital era, the transformation of consumer behavior in shopping habits demands that MSME actors adapt, particularly through online platforms. Unfortunately, many novice entrepreneurs still lack an understanding of how to utilize digital technology, due to limited knowledge, access, or suitable devices. This community service activity aimed to provide basic online selling training for beginner MSME actors to enhance their competitiveness. The training was held on Saturday, April 26, 2025, in a village in Ciamis and was attended by approximately 25 participants, mostly housewives running small home-based businesses. The training adopted a hands-on approach, covering how to create a marketplace account, upload product catalogs, set prices (including the strikethrough pricing feature), and choose appealing product photos. The session was conducted in a relaxed and collaborative atmosphere. More tech-savvy participants assisted those less familiar, despite technical challenges such as limited internet data, slow devices, or poor-quality product photos. High enthusiasm was reflected in the active participation during practice and discussion sessions. Some participants even managed to evaluate their products from a consumer’s perspective. The results of the activity indicate that the training was effective in enhancing basic digital marketing skills among beginner MSME actors.